2009
DOI: 10.1111/j.1468-3148.2009.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Access to Secondary Healthcare for People with Intellectual Disabilities: A Review of the Literature

Abstract: Background There is growing evidence that people with intellectual disabilities have greater healthcare needs than the general population and that these needs are often unmet. Recently, increasing attention has been drawn to poor care received by people with intellectual disabilities when admitted to hospital. Method A literature search was conducted to identify studies on experiences of secondary healthcare for people with intellectual disabilities. Studies were published between January 1990 and March 2008. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 35 publications
0
72
0
1
Order By: Relevance
“…Attention to improving hospital care may include the need to improve communication and information sharing systems. Backer et al (2009) also indicated the need for improved staff knowledge and attitudes. Health care providers receive little education ahout the health care needs of individuals with ID.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Attention to improving hospital care may include the need to improve communication and information sharing systems. Backer et al (2009) also indicated the need for improved staff knowledge and attitudes. Health care providers receive little education ahout the health care needs of individuals with ID.…”
Section: Discussionmentioning
confidence: 95%
“…Access issues included factors related to individuals with ID, such as fear of going to the hospital and communication needs; factors related to the role of caregivers, such as nonrecognition of their knowledge and experience hy hospital staff; the attitudes, knowledge, and communication of hospital staff; and physical environment factors, such as poor layout. Recommendations hased on the integrative review included liaison systems for better coordination of care, improvement of current systems including specific protocols for this population, improvement of staff attitudes and knowledge, improvement of communication and information sharing, and improvements to the physical environment (Backer et al, 2009). The 2001 surgeon general report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…68 There are different models for developing LDLN roles, including posts or teams working in general hospitals; learning disability community teams providing support to people with learning disabilities before, during and after their hospital admission; training hospital nurses to act as a resource ('link nurse') for other hospital staff; and creating city-wide nurse consultant posts to facilitate the provision of co-ordinated care across multisite hospitals. 69 A hospital-based learning disability nurse consultant post has also been described. 70 A national survey of reasonable adjustments made for people with learning disabilities in NHS trusts 36 reported that 55 acute trusts (95%) made use of liaison staff with a specific role in providing health facilitation, such as LDLNs.…”
Section: -67mentioning
confidence: 99%
“…' Understanding the range of communication needs, and development of skills in adapting and using alternative communication -communication is most often cited as an issue (Mencap, 2011;Dinsmore, 2011;Backer et al, 2009;Gibbs et al, 2008), and poor communication poses very significant risks (NPSA, 2004;Read and Johnson, 2012). It can lead to a lack of compliance with care if individuals are not supported to understand (where they are able to).…”
Section: The Scope Of Trainingmentioning
confidence: 98%